Comparative Safety and Immunogenicity of Two Attenuated Enterotoxigenic Escherichia coli Vaccine Strains in Healthy Adults - McKenzie, Robin; Bourgeois, A. Louis; Engstrom, Fayette; Hall, Eric; Chang, H. Sunny; Gomes, Joseph G; Kyle, Jennifer L; Cassels, Fred; Turner, Arthur K; Randall, Roger; Darsley, Michael; Lee, Cynthia; et al. (Infection and Immunity, 2006)
A vaccine against enterotoxigenic Escherichia coli (ETEC) is needed to prevent diarrheal illness among children in developing countries and at-risk travelers. Two live attenuated ETEC strains, PTL002 and PTL003, which express the ETEC colonization factor CFA/II, were evaluated for safety and immunogenicity. In a randomized, double-blind, placebo-controlled trial, 19 subjects ingested one dose, and 21 subjects ingested two doses (days 0 and 10) of PTL-002 or PTL-003 at 2 x 10⁹ CFU/dose. Anti-CFA/II mucosal immune responses were determined from the number of antibody-secreting cells (ASC) in blood measured by enzyme-linked immunospot assay, the antibody in lymphocyte supernatants (ALS) measured by enzyme-linked immunosorbent assay (ELISA), and fecal immunoglobulin A (IgA) levels determined by ELISA. Time-resolved fluorescence (TRF) ELISA was more sensitive than standard colorimetric ELISA for measuring serum antibody responses to CFA/II and its components, CS1 and CS3. Both constructs were well tolerated. Mild diarrhea occurred after 2 of 31 doses (6%) of PTL-003. PTL-003 produced more sustained intestinal colonization than PTL-002 and better IgA response rates: 90% versus 55% (P = 0.01) for anti-CFA/II IgA-ASCs, 55% versus 30% (P = 0.11) for serum anti-CS1 IgA by TRF, and 65% versus 25% (P = 0.03) for serum anti-CS3 IgA by TRF. Serum IgG response rates to CS1 or CS3 were 55% in PTL-003 recipients and 15% in PTL-002 recipients (P = 0.02). Two doses of either strain were not significantly more immunogenic than one. Based on its superior immunogenicity, which was comparable to that of a virulent ETEC strain and other ETEC vaccine candidates, PTL-003 will be developed further as a component of a live, oral attenuated ETEC vaccine.